Expanding the applications of intramedullary cannulated screw fixation in the hand. (May 2023) - Leftley, Chloe; Nikkhah, Dariush; Southall, Clea; Labib, Amir; Moledina, Jamil
Abstract: Objectives: Intramedullary cannulated headless compression screw fixation (ICHCS) is gaining popularity for managing metacarpal and phalangeal fractures, but is still relatively new to the surgical landscape. We aim to further illustrate its utility and versatility by presenting the outcomes of such fractures treated with ICHCS at two tertiary plastic surgery centres. Primary objectives were to assess functional range of motion, patient-reported outcomes, and complication rates. Materials and methods: All patients with metacarpal or phalangeal fractures treated with ICHCS (n = 49) between September 2018 and December 2020 were retrospectively reviewed. Outcomes were active ranges of motion (TAM), QuickDASH scores (obtained via telephone), and complication rates. Two-tailed Student's t-tests evaluated differences between centres. Results: TAMs were available for 59% (n = 34/58) of fractures; 70.7% were metacarpal and 29.3% were phalangeal. The mean cohort metacarpal TAMs and phalangeal TAMs were 237.7° and 234.5°, respectively. QuickDASH scores were available for 69% (n = 34/49) of patients. The mean cohort score for metacarpal fractures was 8.23, and 5.13 for phalangeal. Differences between the two centres were statistically significant (p < 0.05). Two complications occurred, giving an overall complication rate of 3.45%. Conclusion: Our results corroborate previous reports on ICHCS, further demonstrating its versatility and capacity to provide excellent outcomes. More prospective, comparative studies are needed to fully determine the suitability of ICHCS.